Toxoplasma gondii: prevalência de infecção, diagnóstico laboratorial e genótipos - Mattos, Cinara de Cássia Brandão de (2012)
T. gondii is an obligate intracellular parasite and cosmopolitan, whose infection congenital or acquired, results in different forms of toxoplasmosis. The clinical manifestations of this disease are nonspecific and variable. Its diagnosis essentially laboratory is aimed at pregnant women, neonates, patients with immunodeficiencies, patients with eye injury and even normal individuals. Serological methods are often used in the characterization of IgM and IgG anti-T.gondii, but those of nature of molecular favoring genetic characterization of the strains isolated from biological samples. Objectives: The overall objective of this thesis was to investigate the infection by T.gondii in the northwestern region of São Paulo state. Its specific objectives were: 1. to characterize infection in pregnant women, newborns and people with eye diseases 2. to evaluate the applicability of the method of PCR inperipheral blood sample in patients with eye diseases 3. to identify the strains from peripheral blood samples. Casuisitc and Methods: epidemiological data and samples of peripheral blood from patients treated in Outpatient Clinic of High Risk Pregnancy and Retinopathy were collected and analyzed for infection by T. gondii using serological methods (ELISA) and molecular (cnPCR and qPCR). Results: among 574 women with mean age equal to 27.2 ± 6.5, 62% (345/556) showed positive for IgG and 3.4% (n = 19/556) for IgM. In 87 mother-newborn pairs, 64.4% (n = 58) were reactive for anti-T. gondii and 2.3% (n = 2), IgM, 92.9% (52/56) had IgG avidity greater than or equal to 30%. Among 184 patients with different eye diseases, 26% (n = 49) had ocular toxoplasmosis, all reagents for IgG. The PCR (qPCR and cnPCR) applied to the analysis of peripheral blood showed sensitivity and specificity equal to 40.8% and 100%, respectively. Five patients with ocular toxoplasmosis were shown to be infected by the strain toxoDB # 65. Conclusion: The results show that the prevalence of infection with T. gondii in pregnant women, neonates and patients with eye diseases is high in the northwertern region of São Paulo state, and to estimate the rates of congenital infection in the region. In addition to describing the first time the ocular toxoplasmosis in the region, this study reinforces the importance of cnPCR and qPCR methods for the characterization of infection and laboratory strains toxoDB # 65 from peripheral blood samples of patients with chronic infection.